BUDAYA SUPERVISI KEPALA SEKOLAH DENGAN PROFESIONALISME GURU DI SDN TARIK 1 SIDOARJO - Akhmad Sirojuddin (Prodi Manajemen Pendidikan Islam Institut Pesantren KH Chalim Mojokerto, 2020)
This study aims to determine the relationship Supervising Principal with the professionalism of teachers . The study subjects were 13 teachers who serve on SDN I Tarik Village Tarik, Sidoarjo regency. This study is a population. To obtain data on the Supervision of the Principal and Teacher Professionalism, used a questionnaire developed by the researchers. To achieve this goal, the data were analyzed by analysis of the product moment. This research is ex post facto. This study is a population, The population of this study were 13. Data were collected by using questionnaires with Likert scale and documentation. The analytical method used is the product moment analysis. For ease of calculation used SPSS Statistics 21 software. The results showed that : (1) Supervision Elementary School Principal I Tarik Village Tarik, is quite pretty, and the result is 65.38% (2) Professional Teacher SDN I Tarik Village Tarik, Sidoarjo regency quite well. Percentage of the value of questionnaires 79.23%, in the range of 76% -100% that can mean good. (3) There is a relationship between the Principal Supervising Teacher Professionalism SDN I Tarik Village Tarik, Sidoarjo regency. based on calculations that showed the acquisition of 0.366 which means "r" calculation is greater than the table either 5% significance level = 0.235, while the relationship is relatively weak incurred or low. Because based on the "r" calculation is 0.366 lies between 0.20 to 0.40 which interpretation is weak or low correlation.